Trade Liberalization, Social Policy Development and Labour Market Outcomes of Chinese Women and Men in the Decade After China’s Accession to the World Trade Organization - Xiao-Yuan Dong; Shi Li; Sui Yang (United Nations, 2016)
How trade liberalization affects women’s position in the labour market and what role public policy should play to make the process work better for women are among some of the most debated issues in academic communities and in policy-making arenas. This work sheds light on these contentious issues by analysing the trends in labour market outcomes of women and men in China in the decade after its accession to the World Trade Organization (WTO). The publication reviews the changes associated with China’s economic reforms and opening to international trade and investment since the process started in the late 1970s. Since the early 2000s, a wide range of policy measures have been introduced to strengthen labour market regulations, reduce inequality and increase social security. However, most of these policy initiatives were ‘gender neutral’, paying inadequate attention to the institutional constraints that disadvantaged women in the labour market.